2023
DOI: 10.1921/swssr.v24i1.1881
|View full text |Cite
|
Sign up to set email alerts
|

Faith-based organizations' support for older adults in Vietnam: A comparison of Catholic and Buddhist efforts

Abstract: How faith-based organizations (FBOs) take part in the social welfare system for older adults is of interest to policy-makers and researchers in the face of a rapid aging population. Since FBOs are underexplored in Vietnam, this study provides an insightful understanding and analysis of Vietnamese Catholic and Buddhist FBOs’ participation in social service provision to older adults. By conducting secondary data analysis, semi-structured interviews and field observation at some FBOs’ and public social protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…For example, a study by Bankston & Zhou (1995) indicated that strong relations with one's religious social network are associated with higher levels of religiosity on the personal level. Furthermore, Delle Fave et al, 2022 found that the social aspect of the religious community is the most significant factor supporting religious commitment, as those who are more tightly integrated into religious social networks are more dedicated to their faith (Hoang et al, 2021).…”
Section: Thimentioning
confidence: 99%
“…For example, a study by Bankston & Zhou (1995) indicated that strong relations with one's religious social network are associated with higher levels of religiosity on the personal level. Furthermore, Delle Fave et al, 2022 found that the social aspect of the religious community is the most significant factor supporting religious commitment, as those who are more tightly integrated into religious social networks are more dedicated to their faith (Hoang et al, 2021).…”
Section: Thimentioning
confidence: 99%